Multimodal Definition: The Multiplication of Meaning in Electronic Dictionaries - Liu, Xiqin (Lexikos, 2015)
With the popularity of electronic dictionaries, multimodality plays an increasingly important role in lexicography. To broaden the horizons of e-dictionary definitions, this article argues for the establishment of a new term, multimodal definition, as a key component of multimodal lexicography. This term integrates verbal definitions and the complementary multimodal resources from a holistic viewpoint of meaning. In a multimodal definition, a dynamic meaning ecology can be formed, with two critical variables functioning, (semiotic) mode selection and intermodal synergy. In this ecology, meaning expressed verbally can be multiplied in four dimensions: content, form, space and time. Future directions for research are discussed, including dictionary user studies and multimodal corpora. The findings of this article shed light on the construction of a theoretical model for e-lexicography which remains an urgent task in the ongoing digital revolution.